2010
DOI: 10.1074/jbc.m110.183343
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Release to Lumen from ADP-sensitive Phosphoenzyme E1PCa2 without Bound K+ of Sarcoplasmic Reticulum Ca2+-ATPase

Abstract: During

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…This result suggests that the Ca 2ϩ -occluded structure in E1PCa 2 is destabilized in this mutant so that a fraction of the Ca 2ϩ of E1PCa 2 is released rapidly (without affinity reduction because such a rapid release does not occur in 10 M Ca 2ϩ ). Similarly, we previously observed Ca 2ϩ release (escape) from E1PCa 2 without affinity reduction in the wild type in the absence of K ϩ and indicated that the stabilization of E1PCa 2 , in this case by the K ϩ binding on its specific site on the P domain, is crucial for stabilizing the Ca 2ϩ -occluded structure of E1PCa 2 (42 (16,17) (Fig. 8, see the decay after the Ca 2ϩ removal (triangles), although it is still much slower than the wild type (cf.…”
Section: Rapidmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that the Ca 2ϩ -occluded structure in E1PCa 2 is destabilized in this mutant so that a fraction of the Ca 2ϩ of E1PCa 2 is released rapidly (without affinity reduction because such a rapid release does not occur in 10 M Ca 2ϩ ). Similarly, we previously observed Ca 2ϩ release (escape) from E1PCa 2 without affinity reduction in the wild type in the absence of K ϩ and indicated that the stabilization of E1PCa 2 , in this case by the K ϩ binding on its specific site on the P domain, is crucial for stabilizing the Ca 2ϩ -occluded structure of E1PCa 2 (42 (16,17) (Fig. 8, see the decay after the Ca 2ϩ removal (triangles), although it is still much slower than the wild type (cf.…”
Section: Rapidmentioning
confidence: 99%
“…2A in Ref. 42). Therefore, EP decay represents EP isomerization (which is followed by rapid E2P hydrolysis).…”
Section: Rapidmentioning
confidence: 99%
“…5, reflecting the electrostatic component of the activation energy, are almost zero in LiCl or rather negative in choline-Cl. Without the K ϩ , the E1PCa 2 and E2P structures are unstable as noted above (17,36), and the transition between them could occur as a loose, functionally inefficient steric change, where the N-P domain electrostatic interactions could actually restrict, or act as a barrier, for the domain motions. At the physiological ϳ0.1 M K ϩ , the bound K ϩ markedly accelerates the EP transition probably by allowing a sterically restricted precise domain motion in the proper direction guided by the N-P domain electrostatic interactions, thereby accomplishing efficient Ca 2ϩ transport.…”
Section: Roles Of N-p Domain Electrostatic Interactions and Specificamentioning
confidence: 99%